2017
DOI: 10.1016/j.cortex.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses to symmetry presented in the left or in the right visual hemifield

Abstract: Symmetry is a highly salient feature in the visual world, abundant in both man-made and natural objects. In particular, humans find reflectional symmetry most salient. Electrophysiological work on symmetry perception has identified a difference wave known as the Sustained Posterior Negativity (SPN) originating from extrastriate areas. Amplitude is more negative for symmetrical than random patterns, from around 200 msec after stimulus onset. For the first time, we report responses to patterns presented exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Together these results suggest that when attention is directed toward symmetry, responses increase, but when attention is directed away from symmetry, such as during a color task, responses decrease. This task dependence has not emerged strongly from the EEG literature on symmetry (Höfel and Jacobsen, 2007a, 2007b; Jacobsen, & Höfel, 2003; Makin, Rampone, Pecchinenda, & Bertamini, 2013; Makin et al, 2014; Norcia et al, 2002; Rampone, Makin, & Bertamini, 2014; Wright, Makin, & Bertamini, 2017); however, perhaps because of an increased sensitivity of fMRI to attentional effects, we were able to detect such differences here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these results suggest that when attention is directed toward symmetry, responses increase, but when attention is directed away from symmetry, such as during a color task, responses decrease. This task dependence has not emerged strongly from the EEG literature on symmetry (Höfel and Jacobsen, 2007a, 2007b; Jacobsen, & Höfel, 2003; Makin, Rampone, Pecchinenda, & Bertamini, 2013; Makin et al, 2014; Norcia et al, 2002; Rampone, Makin, & Bertamini, 2014; Wright, Makin, & Bertamini, 2017); however, perhaps because of an increased sensitivity of fMRI to attentional effects, we were able to detect such differences here.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible then, that the additional attentional requirements of these trial‐by‐trial color judgements led to a greater suppression of symmetry‐specific responses to slanted stimuli in the study by Makin et al (2015). It is also of note that the measured EEG symmetry response is not always task dependent and can be similar across tasks, whether people are attending to regularity or some other feature such as the color of the dots (Höfel and Jacobsen, 2007a, 2007b; Jacobsen et al, 2003; Makin et al, 2014, 2013; Norcia et al, 2002; Rampone et al, 2014; Wright et al, 2017). Such task‐dependent differences may therefore only emerge for slanted stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to random patterns, symmetrical patterns evoked a more negative-going waveform 250-1000 ms after stimulus onset [10]. In subsequent studies that used different abstract patterns, e.g., dot patterns, these findings extended over different kinds of regularities: reflectional, rotational, and translational symmetry [11][12][13]. This sustained posterior negativity (SPN) differs between the types of regularity.…”
Section: Introductionmentioning
confidence: 97%
“…While the work by Bertamini, Makin, and colleagues (e.g., [10][11][12][13]) suggests an obligatory symmetry processing that is reflected by the SPN, a more diverse pattern arises from the three ERP studies by Höfel and Jacobsen [2,8,15]. While Jacobsen and Höfel [2] observed a double dissociation between the evaluative aesthetic judgment task and the descriptive symmetry judgment task, with a posterior sustained negativity arising only in the symmetry judgment condition, a posterior sustained negativity was observed in the viewing as well as in the evaluative contemplation condition of Höfel and Jacobsen [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, it has been suggested that both the left and the right hemispheres are capable of low-level perceptual processing, and that hemispheric asymmetries arise at later stages of visual processing, in associative areas representing the two sides of visual space [17]. It has to be highlighted, however, that contrasting models have been recently suggested [18,19]. The fact that higher order cortical areas are involved in the detection of symmetrical patterns was confirmed in a functional magnetic resonance imaging (fMRI) study [20]: it was shown that independently of the size and the geometrical configuration of the stimuli, as well as independently of the recruitment of attentional control, symmetrical arrangements activated associative visual areas, in particular V3, V4, V7, and lateral occipital areas (for similar results see also [21,22], for a review see [23]).…”
Section: Introductionmentioning
confidence: 96%